2020
DOI: 10.1002/evl3.200
|View full text |Cite
|
Sign up to set email alerts
|

Herbivory and pollination impact on the evolution of herbivore-induced plasticity in defense and floral traits

Abstract: Theory predicts that herbivory should primarily determine the evolution of herbivore-induced plasticity in plant defenses, but little is known about the influence of other interactions such as pollination. Pollinators may exert negative selection on the herbivoreinduced plasticity of chemical defenses when floral signals and rewards are indirectly affected, provoking deterrent effects on these mutualists. We investigated the influence of constant herbivory and pollination on the evolved patterns and degree of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 64 publications
1
11
0
Order By: Relevance
“…Furthermore, using the same system it has been shown that floral attractiveness i.e., they were more fragrant and displayed larger flowers when evolving in the presence of bumblebees as pollinators. In contrast, when plants grow in the presence of bumblebees and the hervibore Pieris brassicae ( Ramos and Schiestl, 2019 , 2020 ), volatile evolution, production of glucosinolates and autogamy evolve differently. The current emerging hypothesis is a possible coevolution of floral and defense traits.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, using the same system it has been shown that floral attractiveness i.e., they were more fragrant and displayed larger flowers when evolving in the presence of bumblebees as pollinators. In contrast, when plants grow in the presence of bumblebees and the hervibore Pieris brassicae ( Ramos and Schiestl, 2019 , 2020 ), volatile evolution, production of glucosinolates and autogamy evolve differently. The current emerging hypothesis is a possible coevolution of floral and defense traits.…”
Section: Discussionmentioning
confidence: 99%
“…Under this idea, floral traits change due to external factors such as environmental stimuli, biotic stressors, etc. (Rusman et al, 2019a,b;G omez et al, 2020;Ramos & Schiestl, 2020). When this process takes place within dense morphospaces, plastic phenotypes may converge with nonrelated flowers rather than arising as novelties.…”
Section: Plasticity-mediated Floral Convergencementioning
confidence: 99%
“…congesta displays marked local adaptation to browsing and context‐dependent trade‐offs in the fitness value of traits shown to drive population growth and persistence in the presence or absence of deer (Skaien & Arcese, 2020), a pattern thought to occur in other plant‐herbivore systems (e.g. López‐Goldar & Agrawal, 2021; McGoey & Stinchcombe, 2009; Ramos & Schiestl, 2020; Wenk & Falster, 2015).…”
Section: Introductionmentioning
confidence: 99%